(untitled) (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Bats represent approximately one-third of the Brazilian mammal fauna and the Rabies virus has been isolated from 41 of the 167 species of bats present in the country. A Rabies virus independent species-specific variant was detected in 16 insectivorous bats Histiotus velatus in the Southeast of Brazil from 1995 to 2009. The antigenic characterization was made by monoclonal antibodies panel from Centers for Disease Control and Prevention (CDC – Atlanta, USA) and the genetic characterization was performed by sequencing of carboxi-terminal portion of nucleoprotein followed by Maximum Likelihood (ML) genetic analysis with GARLi software. The antigenic characterization made in 12 of these samples showed a unique profile previously described only for the insectivorous bats Histiotus velatus (positive reactivity only with MAb C12 from the utilized panel). The entire 16 samples positive to rabies virus were genetically characterized and they were segregated in the independent monophyletic cluster supported by high bootstrap values. These sequences showed a minimal average intrinsic distance whiting group (1.3%) but they presented low similarity when compared to other lineages circulating in bats and other wild animal lineages from Brazil and worldwide with a range of 8.8% to 25.4%. The antigenic site of the nucleoprotein at residue 377 to 379 (based on PV strain) analysis showed a residue TEV (Thr-Glu-Val) like a some insectivorous bats and different to vampire bats lineage, marmosets lineage and terrestrial cycle related samples. The PV strain shows the amino acids residues TDV (Thr-Asp-Val), D. rotundus isolates show AET (Ala-Glu-Thr) and Marmoset lineage show the amino acids residues TEA (Thr-Glu-Ala). This antigenic variant and genetic lineage has been identified in a large area covering various kilometers and different biomes for at least 14 years between the states of Minas Gerais and Sao Paulo exclusively in this bat species. Surprisingly the system documentation not describe this antigenic variant and genetic lineage found before in other bat species and the Histiotus velatus bat species never ever found before with a different antigenic variant and genetic lineage. The fact of this lineage has been isolated only in this species besides long temporal space and geographically distal to each other, associated with phylogenetic results and previously antigenic data suggest strongly that this rabies virus lineage is associated to Histiotus velatus.